MO282EARLY RENAL RECOVERY AFTER A FIRST FLARE OF PAUCI IMMUNE GLOMERULONEPHRITIS. (29th May 2021) - Zaworski, Jeremy; Vandenbussche, Cyrille; Bataille, Pierre; Hachulla, Eric; Glowacki, Francois; Gibier, Jean baptiste; Daroux, Maïté; Rastimbazafy, Anderson; Bitton, Laura; Humez, Sarah; Guincestre, Thomas; Azar, Raymond; et al.
Abstract: Background and Aims: Renal involvement is a severe manifestation of ANCA-associated vasculitis. Patients often progress to end-stage renal disease. The potential for renal recovery after a first flare has seldom been studied. Our objectives were to describe the evolution of the estimated glomerular filtration rate (eGFR) and identify factors associated with the change in eGFR between diagnosis and follow-up at 3 months (ΔeGFRM0–M3) in a cohort of patients with a first flare of pauci-immune glomerulonephritis. Methods: This was a retrospective study over the period 2003–2018 of incident patients in the Nord-Pas-de-Calais (France). Patients were recruited if they had a first histologically-proven flare of pauci immune glomerulonephritis with at least 1 year of follow up. Kidney function was estimated with MDRD-equation and analysed at diagnosis, 3 rd, 6 th and 12 th months. The primary outcome was ΔeGFRM0–M3. Factors evaluated were histological (Berden classification, interstitial fibrosis, percentage of crescents), clinical (extra-renal manifestations, sex, age) or biological (severity of acute kidney injury, dialysis, ANCA subtype). Results: One hundred and seventy-seven patients were included. The eGFR at 3 months was significantly higher than at diagnosis (mean ± standard deviation, 40 ± 24 vs 28 ± 26 ml/min/1.73 m 2, p < 0.001), with a ΔeGFRM0–M3 of 12 ± 19 ml/min/1.73 m 2 . The eGFR at 12 months was higher than at 3 months (44 ± 13 vs 40 ± 24 ml/min/1.73m 2, p = 0.003). The factors significantly associated with ΔeGFRM0–M3 in univariate analysis were: sclerotic class according to Berden classification, percentage of interstitial fibrosis, percentage of cellular crescents, acute tubular necrosis, neurological involvement. The factors associated with ΔeGFRM0–M3 in multivariate analysis were the percentage of cellular crescents and neurological involvement. The mean increase in eGFR was 2.90 ± 0.06 ml/min/1.73m 2 for every 10-point gain in the percentage of cellular crescents. ΔeGFRM0–M3 was not associated with the risks of end-stage renal disease or death in long-term follow-up. Conclusions: Early renal recovery after a first flare of pauci-immune glomerulonephritis occurred mainly in the first three months of treatment. The percentage of cellular crescents was the main independent predictor of early renal recovery.